The Impact of Sales, Production Costs, and Operating Costs on PT Mayora Indah Tbk Net Income for 2016-2024 - Aulia, Nessa; Fermana, Aldi (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
His study aims to analyze the effect of production costs, operating costs, and sales on net income at PT Mayora Indah Tbk during the 2016–2024 period. The research employed a quantitative approach with secondary data obtained from the company’s annual financial statements. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results indicate that, partially, sales, production costs, and operating costs do not have a significant effect on net income. The F-test also shows that, simultaneously, the three independent variables do not significantly affect net income. The Adjusted R² value of -0.039 suggests that the model used is not sufficient to explain the variation in net income, while the R² value of 0.307 indicates that the variables explain only 30.7% of the variation in net income, with the remaining 69.3% influenced by other factors outside the model, such as exchange rate fluctuations, raw material prices, interest expenses, and global economic conditions. These findings confirm that PT Mayora’s profitability is not solely determined by production costs, operating costs, and sales, but is also largely influenced by external factors